2023
DOI: 10.1108/ajems-09-2022-0372
|View full text |Cite
|
Sign up to set email alerts
|

Digital financial inclusion and economic growth in Sub-Saharan Africa: the role of institutions and governance

Abstract: PurposeThis study examines the role of institutions and governance on the digital financial inclusion and economic growth nexus in Sub-Saharan Africa (SSA) from 2014 to 2020.Design/methodology/approachThis study adopts the generalised method of moments technique which controls for endogeneity. The authors employed four main variables namely, index of digital financial inclusion, gross domestic product per capita growth, institutions and governance.FindingsThe results suggest a significant positive effect of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Previous literature on digital financial inclusion in Africa has increasingly utilized composite indices to assess its progress. However, these studies have been subject to several limitations (Al‐Smadi, 2023; Chinoda & Kapingura, 2023a, 2023b; Khera et al, 2022), underscoring the need for more comprehensive and nuanced evaluations of this critical development issue.…”
Section: Africa's Digital Financial Inclusion Journey: a Comparative ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature on digital financial inclusion in Africa has increasingly utilized composite indices to assess its progress. However, these studies have been subject to several limitations (Al‐Smadi, 2023; Chinoda & Kapingura, 2023a, 2023b; Khera et al, 2022), underscoring the need for more comprehensive and nuanced evaluations of this critical development issue.…”
Section: Africa's Digital Financial Inclusion Journey: a Comparative ...mentioning
confidence: 99%
“…Moreover, the existing literature on digital financial inclusion in Africa has predominantly relied on either theoretical framework (Isukul & Tantua, 2021; Mhlanga, 2020; Telukdarie & Mungar, 2023), descriptive approaches (Agwu, 2021; Machasio, 2020) or macro‐level analyses (Beyene Fanta & Makina, 2019; Chinoda & Kapingura, 2023a, 2023b; Khera et al, 2022; Kouladoum et al, 2022; Tok & Heng, 2022). However, no study has successfully achieved the following three significant objectives in the realm of digital financial inclusion in Africa to date: (1) quantifying the level of digital financial inclusion in Africa in the post‐COVID‐19 era; (2) exploring the microeconomic determinants of the region's access and usage of digital financial services; and (3) identifying potential barriers that may impede African citizens from reaping the benefits of digital financial services.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad and Law (2023) have shown that regardless of geographic location, countries with similar institutional characteristics exhibit the same levels of economic growth. Chinoda and Kapingura (2023) certified that institutions and governance exert positive effects on the relationship between financial inclusion and economic growth. Gyamfi et al (2022) demonstrated that in an environment with poor institutional quality, the effect of financial development on economic growth is negative.…”
Section: Institutional Quality and Economic Growthmentioning
confidence: 99%
“…The rapid expansion of ICT has reformed the nancial industry landscape with digital technologies, and nancial services can be relinquished in further e cient and less expensive pathways (Chinoda and Kapingura 2023; Niu et al 2022; Geng and He 2021). For instance, rather than establishing physical branches like bank outlets, nancial institutions can extend a diverse array of digital services to a wide customer base accessible through computers, smartphones, and other electronic devices (Niu et al 2022; Chinoda and Kapingura 2023). The ICT's integration with nance holds the potential to enhance nancial inclusion by inviting more individuals, especially those traditionally underserved, into the contemporary nancial system (Niu et al 2022;Liu et al 2021).…”
Section: Introductionmentioning
confidence: 99%